Measurement of intellectual capital as exemplified by methods of groups based on the ROA indicator and on market capitalization - Karolina Palimąka; Mateusz Mierzejewski (e-Finanse: Financial Internet Quarterly, 2016)
The concept of a knowledge-based economy is a relatively new topic, but it does not mean that the previous economies did not use knowledge. For many years, knowledge formed the basis of any economy, it was a factor that set the pace of each of them, but just nit is making a significant impact on the entrepreneurial environment, and more. Inherent KBE is the concept of intellectual capital. The article raises both theoretical approaches towards the concept of intellectual capital, and points to the importance (from the point of view of managing this intangible value in the company) -of measuring intellectual capital. The process of good management of the value of intangible assets must be supported by knowledge about, e. g., its size, value, etc. The authors focus on presenting methods of measuring intellectual capital from two groups of methods by the classification made by K. E. Sveiby, who is considered one of the fathers of the IC concept. The goal of the article is to compare methods from these two groups in terms of their flaws and advantages as regards preparing business analysis. This is done through presentation of the topic, including the concept and methods of intellectual capital measurement, which was based on the review of the literature. Furthermore, based on financial statements of companies from the WIG- oil &gas index and WIG- food industry index ways of interpreting the final results are presented.
Keywords: D24; E22; M49; O34; 330; intellectual capital; IC; knowledge based economy; measurement of IC; MV/BV; CIV; oil&gas industry; food industry; WIG - index